Does Cell Size Impact Chloroplast Genome Size? - Smith, David R. (Frontiers in Plant Science, 2017)
There is a strong positive relationship between nuclear genome size and cell size across the eukaryotic domain, but the cause and effect of this relationship is unclear. A positive coupling of cell size and DNA content has also been recorded for various bacteria, suggesting that, with some exceptions, this association might be universal throughout the tree of life. However, the link between cell size and genome size has not yet been thoroughly explored with respect to chloroplasts, or organelles as a whole, largely because of a lack data on cell morphology and organelle DNA content. Here, I speculate about a potential positive scaling of cell size and chloroplast genome size within different plastid-bearing protists, including ulvophyte, prasinophyte, and trebouxiophyte green algae. I provide examples in which large and small chloroplast DNAs occur alongside large and small cell sizes, respectively, as well as examples where this trend does not hold. Ultimately, I argue that a relationship between cellular architecture and organelle genome architecture is worth exploring, and encourage researchers to keep an open mind on this front.